Morbidity following salvage esophagectomy for squamous cell carcinoma: the MD Anderson experience. Issue 3 (17th July 2019) - Mitchell, K G; Nelson, D B; Corsini, E M; Vaporciyan, A A; Antonoff, M B; Mehran, R J; Rice, D C; Roth, J A; Sepesi, B; Walsh, G L; Bhutani, M S; Maru, D M; et al.
SUMMARY: The survival advantage associated with the addition of surgical therapy in esophageal squamous cell carcinoma (ESCC) patients who demonstrate a complete clinical response to chemoradiotherapy is unclear, and many institutions have adopted an organ-preserving strategy of selective surgery in this population. We sought to characterize our institutional experience of salvage esophagectomy (for failure of definitive bimodality therapy) and planned esophagectomy (as a component of trimodality therapy) by retrospectively analyzing patients with ESCC of the thoracic esophagus and GEJ who underwent esophagectomy following chemoradiotherapy between 2004 and 2016. Of 76 patients who met inclusion criteria, 46.1% (35) underwent salvage esophagectomy. Major postoperative complications (major cardiovascular and pulmonary events, anastomotic leak [grade ≥ 2], and 90-day mortality) were frequent and occurred in 52.6% of the cohort (planned resection: 36.6% [15/41]; salvage esophagectomy: 71.4% [25/35]). Observed rates of 30- and 90-day mortality for the entire cohort were 7.9% (planned: 7.3% [3/41]; salvage: 8.6% [3/35]) and 13.2% (planned: 9.8% [4/41]; salvage: 17.1% [6/35]), respectively. In summary, esophagectomy following chemoradiotherapy for ESCC at our institution has been associated with frequent postoperative morbidity and considerable rates of mortality in both planned and salvage settings. Although a selective approach to surgery may permit organ preservation in many patients with ESCC, these results highlight that salvage esophagectomy for failure of definitive-intent treatment of ESCC may also constitute a difficult clinical undertaking in some cases.